Russian Literature on Cinema (Short Essay) - Izvolov Nikolai A. (Художественная культура)
The article suggests that literature about cinema depends very much on cinema, and not only on its repertoire, but also on more significant, deeper issues. This idea is considered by the example of various types of books and magazines published in our country in different historical periods: the pre-revolutionary period, the Soviet period, and the post-Soviet period, which continues to this day. The first part of the article discusses the pre-revolutionary period of the Russian film press, the first examples of theoretical thought — the articles by Maxim Gorky and the books by Boleslav Matushevsky, and the appearance of the first specialized film magazines. The main part is devoted to the period of Soviet cinema, which was marked by the greatest number of technological and aesthetic achievements of Russian cinema, the appearance of works of cinematographic art and various types of printed products on cinema. The final part traces the modification of cinematographic publications in the post-Soviet period and their gradual integration into the technologies of the digital period.